Effects of Railway Noise on Residents’ in A Residential Area - Ria Anggreani Syahputri; Budi Damianto (Applied Research on Civil Engineering and Environment (ARCEE), 2021)
Population growth in Depok City is large and not in accordance with development land causes many residents’ to build houses with conditions <5 meters from the line of Electric Rail Train or Kereta Rel Listrik (KRL); this causes changes in the quality of the environment, including noise. The objective of this study is to determine the noise level, and the results will be compared with the standard noise level of the residential area; also, to find the influence of noise on residents’. This research was conducted in the area of ​​Rawa Geni Raya Street, 1st Neighborhood, Ratu Jaya Urban Village, Depok City. Noise measurements were carried out at 5-points using a simple method with a noise level measuring instrument (SLM). At one time, the measurement was taken for 10 minutes with a reading time of every 5 seconds. The questionnaire was measured using a Purposive Random Sampling technique, and the number of samples was calculated using the Slovin formula. The results of this study indicate that the 5-point noise level exceeds the recommended threshold according to KEPMEN LH 48 of 1996 and PERMENKES 718/1987 at  55 dB(A). The largest value for the 24-hour noise level (LSM) is at point 1, which is 5 m from the KRL line. The noise level on the weekday is 75.32 dB(A) and 74.24 dB(A) on weekends. According to PERMENKES No 718/1987, the location of point 1 should be included in Area D as an industrial zone, plant, railway station, and bus terminal. The results of questionnaires by 34 respondents showed that the noise generated by KRL was noisy and the majority of respondents agreed the noise affected the comfort level; in terms of health, respondents agreed KRL noise caused sleep disturbances and hearing loss.